Safety of Using Traditional Chinese Medicine Injections in Primary Medical Institutions: Based on the Spontaneous Reporting System 2016–2020 in Henan Province, China - Yan, Ziqi; Feng, Zhanchun; Jiao, Zhiming; Wang, Ganyi; Chen, Chaoyi; Feng, Da (Frontiers in Pharmacology, 2022)
Abstract Objective: Traditional Chinese medicine (TCM) injection is widely used, but its adverse drug reaction (ADR) may be a serious public health concern in primary medical institutions. This research will explore the safety of TCM injections and provide clinical recommendations at the primary medical institutions. Method: ADR data were collected by the Henan Adverse Drug Reaction Monitoring Center from 2016 to 2020 were analized Descriptive statistics, chi-square analysis, binary logistic regression, and Mantel-haenszel hierarchical analysis were used to identify the risk factors associated with the rational use of TCM injections in primary medical institutions. Results: A total of 30839 cases were collected in this study, 4905 cases (15.90%) were SADRs. Patients using TCM injections in primary medical institutions were more likely to cause SADRs (OR=1.149, 95%CI:1.061-1.245). Aged over 60 years (OR=1.105, 95%CI:1.007-1.212), non-essential drugs (OR=1.292, 95%CI:1.173-1.424), autumn (OR=1.194,95%CI:1.075-1.326) and TCM injections with safflower (OR=1.402, 95%CI:1.152-1.706), danshen (OR=1.456, 95%CI:1.068-1.984) and medication reasons with chemotherapy (OR=2.523, 95%CI: 1.182-5.386) and hypertension (OR=1.495, 95%CI: 1.001-2.233) were more likely to suffer SADR in primary medical institutions. Conclusions: In general, the number of reported cases of TCM injection was declining over time, but the proportion of SADRs in primary medical institutions increased. In the future, it is necessary to continue to restrict TCM injections at the macro policy level, and vigorously promote the varieties in the essential drug list. At the micro level, it is necessary to intervene in specific populations, specific diseases and specific drugs, first start with them, step by step, and effectively prevent SADR occurrences in primary medical institutions. Keywords: TCM injections; ADRs; primary medical institutions; Medication behavior